(untitled) (Journal of Politics and International Studies, 2023)
Cyber-warfare attacks are not commonly found like cyber-attacks yet it done by countries, organizations or institutions to disrupt the activities of their enemies in the cyberspace also safeguarding their own information assets. The current study has adopted documentary analysis by using content analysis as method of analysis. The researcher has searched through relevant databases; Google Scholar, JStor and Emerlad Insight by formulating key-terms for search. The study found that the measures taken by the governments usually can be categorized into two types; repressive measures and soft measures. The repressive measures can be defined as denial of access of internet services and blockage of websites and social media pages run by the terrorists. This also includes the blockage and restriction of the promotion of radical content and ideas to the common people.